2015
DOI: 10.1002/gepi.21936
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Genetic Predisposition of Education on Myopia: A Mendelian Randomization Study

Abstract: Myopia is the largest cause of uncorrected visual impairments globally and its recent dramatic increase in the population has made it a major public health problem. In observational studies, educational attainment has been consistently reported to be correlated to myopia. Nonetheless, correlation does not imply causation. Observational studies do not tell us if education causes myopia or if instead there are confounding factors underlying the association. In this work, we use a two-step least squares instrumen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
67
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 62 publications
(75 citation statements)
references
References 49 publications
5
67
0
1
Order By: Relevance
“…However, the possibility of a number of genes of small effect, perhaps inherited simultaneously and linked, that control neural signaling influencing ocular growth and learning abilities remains interesting. Recent research has identified gene-environment interactions between educational attainment and myopia48, whilst PRS for educational attainment predict refractive error and when incorporated as an instrumental variable in Mendelian randomization (MR) analysis support the notion that educational attainment is causally related to refractive error49. The education PRS in the MR study only explained 0.25% of refractive error variance, comparatively less than the variance explained by IQ in our analysis.…”
Section: Discussionsupporting
confidence: 60%
“…However, the possibility of a number of genes of small effect, perhaps inherited simultaneously and linked, that control neural signaling influencing ocular growth and learning abilities remains interesting. Recent research has identified gene-environment interactions between educational attainment and myopia48, whilst PRS for educational attainment predict refractive error and when incorporated as an instrumental variable in Mendelian randomization (MR) analysis support the notion that educational attainment is causally related to refractive error49. The education PRS in the MR study only explained 0.25% of refractive error variance, comparatively less than the variance explained by IQ in our analysis.…”
Section: Discussionsupporting
confidence: 60%
“…In our study, a higher prevalence of myopia was found in the population with a secondary or higher level of education, although in the multivariate analysis this association was not statistically significant (OR 1.14, 95% CI 0.86 to 1.52). Recently, Cuellar-Partida et al used a Mendelian randomisation approach and suggested that observational studies, such as the one we conducted, could underestimate the true effect of educational level on the prevalence of myopia in populations 21. In the case of hyperopia, in our study, the highest educational level was shown as protective (OR 0.59, 95% CI 0.47 to 0.74).…”
Section: Discussionmentioning
confidence: 43%
“…[66] In the former study, low serum 25(OH)D levels were significantly associated with myopia, especially high myopia in adolescents in Korea. [36] The population in the previous study was in their growth period and myopia was progressing; most studies seeking the cause of myopia are targeted at this age group, [3,10,15,18,40,47] whereas the present study targeted a large adult population in which ocular growth was complete. In this regard, 25(OH)D and sun exposure levels may have different mechanisms in the prevalence of myopia and exert independent effects on myopia.…”
Section: Discussionmentioning
confidence: 96%
“…[79] Although the cause of myopia is as yet unclear, genetic and environmental factors may contribute to its development. [1015] Some recent studies suggested that increasing time spent outdoors may prevent the development of myopia, [1417] although the results of some epidemiological studies oppose this theory. [18,19] …”
Section: Introductionmentioning
confidence: 99%